EFEKTIVITAS FORUM GENRE DALAM MENINGKATKAN KESEHATAN REPRODUKSI REMAJA KABUPATEN SUMEDANG - Edy Herdiana (FISIP Universitas Sebelas April, 2022)
This study aims to examine the effectiveness of the work of the GenRe Forum in improving adolescent reproductive health at Sumedang Regency, the barriers to its effectiveness, and efforts to overcome these obstacles. The method used in the preparation of this research report is a qualitative research method with a descriptive type. The sampling technique used was purposive sampling, with research informants: Head of Family Planning, Head of Adolescent Reproductive Health Section, and General Chair of the GenRe Forum. Data collection techniques through library research and field studies. In analyzing the data, the Miles and Huberman model used the following steps: data reduction, data presentation, conclusion drawing/verification, and triangulation. Based on the results of the study, it was concluded that the GenRe Forum carried out all its activities effectively. However, the implementation is currently experiencing several obstacles, including those related to the implementation of the GenRe Forum being disrupted due to the Covid-19 pandemic so that some activities are temporarily delayed. In addition, the lack of budget allocation so that the facilities used cannot be fully met. In overcoming these obstacles, several efforts were made, including conducting evaluation meetings on each activity that has been carried out and the provision of facilities from the Office regarding the provision of budgets to fulfill the needs of the GenRe Forum in carrying out future activities. Suggestions in connection with this research is that it is hoped that knowledge and ability to implement it in improving reproductive health can be further improved so that its work effectiveness can run in accordance with the desired results.